Model pangkalan data bagi tuntutan kecederaan peribadi (TKP) di Malaysia (Personal injury claims (PIC) database modelling in Malaysia) / Syadatul Syaeda Mat Saleh …[et al.] - Mat Saleh, Syadatul Syaeda; Awang @ Ali, Najihan; Nik Mustapa, Nik Ruslawati; Jamian, Nurul Husna; Abdul Hamid, Hussin (Universiti Teknologi MARA, 2020)
Road accident is not stranger matter in Malaysia. Subsequently, often leads to a claim for personal injury by the persecuted party. In Malaysia, the method for calculating claims applies a multipliermultiplicand approach. This approach is no longer relevant and unfair to the claimant as it excludes personal status in the quantum calculation of damages. Hence, this study uses the Ogden Table as introduced in the United Kingdom as benchmarking guidelines, by taking into account of all aspect of claimant's personal condition for the purpose of such calculation. This study is built upon a proposed framework of data modelling system known as Entity Relationship Diagram (ERD) and the created process modelling known as data flow diagram (DFD). Doing so, the claimants will insert their input data, run it through the first process, and store the information in the claim injury part database. 76 They can also edit and store to claim injury part database on their own. This will generate a report with the information in claim injury part database and can be viewed by claimant, court and lawyer as target users. It is hoped that it will facilitate the calculation of injury claim which would serve justice and accuracy of personal injury in road accidents.